Wind Tunnel Study on Wind-Induced Vibration Responses of a UHV Transmission Tower-Line System. Issue 7 (July 2013) - Deng, H.Z.; Si, R.J.; Hu, X.Y.; Duan, C.Y.
This paper presents an experimental investigation on the wind-induced vibration of a transmission tower-line system. A discrete stiffness method is applied to design the aero-elastic model on the basis of similarity theory. The dynamic characteristics of the single tower and the tower-line system are identified and the displacement responses at different positions are obtained under a variety of wind speeds. The mean and the RMS of the displacements as well as their spectra are discussed. Moreover, the test results and the codal specifications are compared in terms of the wind-induced vibration coefficient. The first natural frequency of the single tower is slightly larger than that of the tower-line system. But the damping ratio of the former is smaller than that of the latter, especially in the direction normal to the conductors. At the wind attack angle of 90°, the conductors significantly increase the longitudinal and lateral displacement RMS as well as the longitudinal mean displacement. And more complicated forms of vibration are aroused by the conductors, especially in the lateral direction. The wind-induced vibration coefficient show a notable rise at the position of cross arm, which cannot be characterized by Chinese code. Besides, the wind-induced vibration coefficient specified by the code is much smaller than test results thus the codal value seems to be unsafe for the UHV transmission tower.